Identification of Staphylococcus piscifermentans from dog feces - Stetina, V; Lauková, A; Strompfová, V; Svec, P; Sedlácek, I (Folia microbiologica, 2005)
The AD 2 strain isolated from feces of a healthy dog in Slovakia was characterized phenotypically by the conventional tests and commercial identification kits API Staph and ID32 Staph. Results of biochemical tests identified the strain as S. piscifermentans, fully corresponding with the species description. Further characterization by whole-cell protein profile analysis (SDS-PAGE) confirmed the identification based on biochemical tests and showed that the AD 2 strain is S. piscifermentans; lactic acid production, urease activity, bacteriocin production and the antibiotic susceptibility of it were also determined. S. piscifermentans AD 2 isolated first from an animal source was deposited in the Czech Collection of Microorganisms as Staphylococcus piscifermentans CCM 7165.
Keywords: Feces; Reagent Kits, Diagnostic; Animals; bakteriální proteiny; psi; fermentace; Bacterial Typing Techniques; Food Microbiology; Bacterial Proteins; Microbial Sensitivity Tests; Fermentation; feces; Anti-Bacterial Agents; Fishes; zvířata; potravinářská mikrobiologie; Dogs; ryby; reagenční diagnostické soupravy; Staphylococcus; mikrobiální testy citlivosti; antibakteriální látky; techniky typizace bakterií